KUALITAS PERTUMBUHAN Eucalyptus sp. DARI PERBANYAKAN VEGETATIF DAN GENERATIF - Pasaribu, Desi Indriani; Sulaeman, Rudianda; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Eucalyptus sp. is fast growing species reproduced in industrial vegetation forest (IVF) as the raw material for the production of pulp and paper. In order to support the availability of raw material, an effort to increase the stands productivity is carried. In this case, one of the methods is by doing plant breeding with both vegetative and generative ways. The purpose of this research is to analyze the difference in the growth level and the quality of the fiber of the Eucalyptus sp. based on the generative and vegetative method in reproduction.This research using  Randomized Complete Block Design (RCBD) consist of two (2) treatmens and four (4) replications and ten (10) units trial. The result of the research shows that vegetative growth is better than the generative growth with the average of vegetative growth for its length is 0.55 m and the average of growth for its diameter is 0.53 cm while the average of the generative growth for its length is 0.15 m and average of the growth for its diameter is 0.13 cm. The quality of the fiber of the Eucalyptus sp. with vegetative method is longer than the generative method. Keywords: Eucalyptus sp., vegetative, generative, length of fibre